2020
DOI: 10.4236/ce.2020.113030
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Brazilian Education: Review of a Decade of Literature

Abstract: The present study resulted from the analysis of a large array of investigative products focused on creativity in higher education. A systematic review of studies between 2008 and 2018 found 27 theses published by doctoral programs in the specific field of education. Twenty-five Brazilian scientific databases were analyzed using a qualitative approach aimed at mapping creativity in higher education, demonstrating longitudinally how, when, who and with what purposes creativity has been the object of study. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…Dessa forma a transição para o remoto torna-se suscetível a geração de custos adicionais a esses, com a compra de computadores e contratação de Internet. [17][18][19] O trabalho remoto em casa pode acabar sendo realizado em locais inadequados como nos sofás e mesas da cozinha com presença de familiares, e vulneráveis a interrupções. Sendo importante um local privativo para o trabalho em casa, na qual haja tranquilidade e possa-se trabalhar por longos períodos.…”
Section: Discussionunclassified
“…Dessa forma a transição para o remoto torna-se suscetível a geração de custos adicionais a esses, com a compra de computadores e contratação de Internet. [17][18][19] O trabalho remoto em casa pode acabar sendo realizado em locais inadequados como nos sofás e mesas da cozinha com presença de familiares, e vulneráveis a interrupções. Sendo importante um local privativo para o trabalho em casa, na qual haja tranquilidade e possa-se trabalhar por longos períodos.…”
Section: Discussionunclassified
“…Com a suspensão das aulas presenciais, o surgimento do ensino remoto emergencial respondeu aos anseios pela continuidade da aprendizagem fora do espaço escolar, momento em que de acordo com Berg et al (2020) Essa saída emergencial se tornou uma alternativa educacional (em muitos casos, a única) para que não se perdesse o vínculo entre escola, aluno e conhecimento (BRASIL, 2020; UNESCO, 2020) e tentar cumprir os conteúdos básicos das grades curriculares dentro do período de pandemia. Porém, como afirma Costa (2020), esse tipo de ensino necessita da utilização de recursos tecnológicos e precisa estar adaptado à realidade tecnológica de cada aluno para que se realize e é nesse sentido, que o ensino remoto se tornou desafiador para diversos sistemas educacionais.…”
Section: Do Ensino Remoto Ao Retorno àS Aulas Presenciais: a Educação...unclassified
“…Martínez (2002) points that the school is an essential local on development and expression of creativity, requiring of planning of interventions that may develop the creativity and change the school itself too. However, a recent study of Berg et al (2020) demonstrated that, in Brazil, the higher education (in which one it is expected a pattern to be followed by the other education levels) still there is a lot to produce and understand about creativity, once it is noticed a possible delay on creativity and learning relation. Other authors have been already reported this aspect of creativity in Brazil in other education levels (Wechsler, 2002;Bahia & Trindade, 2013) pointed that exists barriers to its development.…”
Section: Vygotsky's Understandment and The Educationmentioning
confidence: 99%